Professional Development Of Professors Of Prospective Teachers In Brazil | Desarrollo Profesional De Futuros Formadores De Profesores En Brasil - Richit, Adriana; Xavier de Almeida, William (Revista Neiba, Cadernos Argentina Brasil, 2024)
ABSTRACT This article examines the opportunities for the professional development of professors of future teachers determined by the legal regulations concerning teacher education in higher education and the actions and programs of agencies related to the Ministry of Education dedicated to higher education. The analysis is supported by the concept of professional development outlined by Christopher Day, and by principles presented by Thomas Guskey and their significance for the concept of teacher professionalism. The analysis focuses on a set of official documents found in archives associated to the Ministry of Education, which constitute the empiric material for the study. Two perspectives were identified concerning the process of professional development of university professors. The first is that the university is a locus for the development of educators of future teachers, as the space for the realization of graduate and post-doctoral programs, and institutional and interinstitutional partnerships, and by providing professors-educators different professional experiences with teaching, research, extension and institutional administration. The second is the development of professors is realized through research and the production of knowledge, indicated by the fact that the incentives are found in the distribution of grants for research, and graduate and post-doctoral studies. Keywords: Professional development of professors; educators of future teachers; higher education. RESUMO El artículo examina las posibilidades de desarrollo profesional de los formadores de futuros docentes que surgen del ordenamiento jurídico relacionado con la formación docente de educación superior y de las acciones y programas de organismos vinculados al Ministerio de Educación orientados a la educación superior. El análisis se sustenta en el concepto de desarrollo profesional esbozado por Christopher Day, así como en los principios presentados por Thomas Guskey y sus desarrollos en el concepto de profesionalismo docente. El análisis se centró en un conjunto de documentos oficiales, extraídos de repositorios oficiales vinculados al Ministerio de Educación, que constituyeron el material empírico del estudio. Como resultado, el análisis mostró dos perspectivas para el proceso de desarrollo profesional de los profesores universitarios: la universidad es el locus para el desarrollo del docente de los futuros profesores, ya sea como instancia para la realización de programas de posgrado, posdoctorado, alianzas institucionales e interinstitucionales, además de brindar oportunidades para que el docente docente tenga diferentes experiencias profesionales en docencia, investigación, extensión y gestión institucional; El desarrollo del formador se logra a través de la investigación y la producción de conocimiento, ya que los incentivos se concentran en la distribución de becas de investigación, posgrado y posdoctorado, así como promover la investigación a través de la distribución de recursos y premios de obras. Palavras-chave: Desarrollo profesional docente; formadores de futuros profesores; educación universitaria.